DETERMINAN LOAN AT RISK: MITIGASI DAN PENGELOLAANNYA: Magister Manajemen Pascasarjana Universitas Triatma Mulya, Bali - I Wayan Budi Artha; I Putu Santika; Surya Nugraha (Journal of Applied Management and Accounting Science, 2023)
The purpose of this study is to analyze and empirically prove the influence of company internal factors / Bank specific (capital and performance) and company external factors / macroeconomics (economic growth and inflation) on Loan at Risk (LAR), including mitigation and management models in state-owned banks. The research period is 2012 – 2021, the sampling technique is saturated sampling, all members of the population are used as samples. The results of the study show that the Loan at Risk of state-owned banks is influenced by performance, economic growth and inflation. Loan at Risk to be properly mitigated and controlled. The handling must be carried out in an integrated and sustainable manner by the business line (RM) and risk line (CRM), starting from current loans to bad loans, and assisted by technology (digitalization) so that the settlement or recovery can be faster and optimal